Performance of pitcher-type POU filters for the removal of 75 PFAS from drinking water: comparing different water sources - Teymoorian, Termeh; Dinh, Quoc Tuc; Barbeau, Benoit; Sauvé, Sébastien (Frontiers in Environmental Chemistry, 2024)
This study presents a comprehensive assessment of the performance of popular pitcher-type point-of-use (POU) water filters to remove PFAS contaminants from tap waters. The evaluated filters, Brita (Elite and Standard), ZeroWater, Aquagear, and ClearlyFiltered, were tested for their efficacy in removing 75 targeted PFAS, total organic carbon (TOC), total dissolved solids (TDS), chloride, and sulfate from two Canadian tap waters with background Σ75 PFAS concentrations of 13 and 56 ng/L. Overall, the performances of the filters varied depending on the structure of the filter media, the water source, and the specific contaminants present. ZeroWater was the top performer in the case of total PFAS removal. The volume-weighted average removal of total PFAS after 160 L of filtration using Saint-Donat tap water was 99% for ZeroWater, 99% for ClearlyFiltered, 77% for Aquagear, and 20% for Brita (Elite). In the case of Montreal tap water, which had different water characteristics and lower total PFAS levels, the volume-weighted average removal for PFAS was ≈100% for ZeroWater, 96% for ClearlyFiltered, 60% for Aquagear, 48% for Brita (Elite), and 38% for Brita (Standard). Both laboratory and home tests involving ZeroWater filters yielded similar high-performance results using Montreal tap water. Although ZeroWater exhibited high PFAS removal (99%) in Saint-Donat water, TDS and TOC desorption and a significant drop in pH were observed after 80 L, a phenomenon which was explained by the higher total concentration of anions in this water. In contrast, no desorption was observed in Montreal tap water for TDS and TOC due to the lower concentrations of anions. The Aquagear filter demonstrated an unusual increase in concentrations of sulfate after the initial 20 L, which needs further evaluation. This study discusses individual filter performance, the influence of tap water characteristics, and the potential to meet the new NSF guidelines, which provides valuable insights for consumers seeking to choose an appropriate easy-to-use water filtration system to ensure safe and clean drinking water in different regions.